2015
DOI: 10.4236/ojss.2015.59019
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Cow Manure Vermicompost and NPK Fertilizers and on the Growth and Production of Zinnia (Zinnia elegans) Flower

Abstract: A pot experiment was conducted to investigate the comparative effect of cow manure vermicompost and NPK fertilizers on the growth and flower production of Zinnia (Zinnia elegans). An air dried sandy loam soil was mixed with four rates of NPK fertilizer equivalent to 0 (control), 0.5 dose (N-P-K = 69-16-35 kg•ha −1), 1 dose (recommended) (N-P-K = 137-32-70 kg•ha −1), 2 doses (N-P-K = 274-64-140 kg•ha-1) and 4 doses (N-P-K = 548-128-280 kg•ha −1) and three rates of vermicompost equivalent to 5%, 10%, 20% by oven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
3
6
0
3
Order By: Relevance
“…This is in agreement with the findings of [29] who indicated that Potassium plays several roles in plant metabolism, and to perform these roles positively, it should interact positively with other essential nutrients. Potassium plays an important role in many biochemical and physiological processes in crop plants [30,54]. Among these processes rapid assimilation of absorbed NH 4 + ions, ensure pH stabilization, osmoregulation, membrane transport processes, and enzyme activation.…”
Section: Days To 50% Tasseling Silking and Maturity Of Maizementioning
confidence: 99%
“…This is in agreement with the findings of [29] who indicated that Potassium plays several roles in plant metabolism, and to perform these roles positively, it should interact positively with other essential nutrients. Potassium plays an important role in many biochemical and physiological processes in crop plants [30,54]. Among these processes rapid assimilation of absorbed NH 4 + ions, ensure pH stabilization, osmoregulation, membrane transport processes, and enzyme activation.…”
Section: Days To 50% Tasseling Silking and Maturity Of Maizementioning
confidence: 99%
“…A adequada oferta de nutrientes reflete em maior desenvolvimento dos órgãos vegetativos e reprodutivos, uma vez que essas substâncias fazem parte do complexo sistema fisiológico das plantas e seus processos, tais como a fotossíntese, produção de proteínas, ativação de enzimas, divisão e expansão celular, entre outros (Taiz et al, 2017). Para plantas de Zinnia elegans, observa-se resposta positiva no desenvolvimento vegetativo e na qualidade das flores com a utilização de fertilizantes minerais e orgânicos (Chattopadhyay, 2014;Elhindi et al, 2016;Mladenović et al, 2015;Sultana et al, 2015), aumentando seu valor de comercialização.…”
Section: Resultsunclassified
“…Portanto, estes devem ser compostos por elementos que favoreçam o adequado desenvolvimento, favorecendo às características de valor comercial das espécies, tais como flores, folhas, entre outros. No caso específico da espécie Zinnia elegans, observa-se grande variação das características biométricas dos órgãos vegetativos e das flores, dependendo das condições de cultivo, com destaque para o substrato utilizado durante seu desenvolvimento (Sardoei et al, 2014;Sultana et al, 2015;Pallavi et al, 2017).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…On the other hand, Sönmez et al (2013) observed that the highest leaf length (47.9 cm), the highest plant length (70.6 cm), and the highest leaf length 30.78 mm) was obtained in waste mushroom compost application, in the case of gladioli plant. Sultana et al (2015b) observed that the results showed that the rate of effects within NPK fertilizers and worm fertilizer treatments were not found significant on leaf length of (Zinnia elegans) flowers. However, Keisam et al (2014) observed that leaf length of gladioli was greatly influenced by different combinations of organic and inorganic fertilizers.…”
Section: Leaf Length (Mm)mentioning
confidence: 92%